RANCANG BANGUN SMART TRASH BIN BERBASIS ARDUINO DAN MODUL GSM - Feri susilawati (Politeknik Aceh, 2019)
Lack of public awareness in maintaining cleanliness is a problem faced by cleaning staff. Where every day cleaning staff must collect the garbage that is disposed of not in its place. The solution chosen was wrong only by attracting the interest of the community in the practice of disposing of trash in its place, designed as attractive as possible with “SMART TRASH BIN BERBASIS ARDUINO DAN MODUL GSM”, Where this tool functions automatically and the public can be disposed of garbage at the shelter without having to open and closes. This SMART TRASH BIN can also help cleaning staff by sending SMS to officers with information